RNA localization regulates diverse and dynamic cellular processes - Ryder, Pearl V.; Lerit, Dorothy A. (Traffic (Copenhagen, Denmark), 2018)
RNA localization is a fundamental paradigm used to compartmentalize gene activity within diverse cellular contexts. When coupled to translational control, the localization of messenger RNA (mRNA) generates localized protein enrichments within cells. Long appreciated for its role in neurogenesis and embryo development, RNA localization is evolutionarily conserved across taxa and contributes to a myriad of cellular responses, including polarization, adhesion, migration, proliferation, host‐pathogen interactions, the stress response and more. Here, we summarize the importance of mRNA localization to diverse cellular responses referencing several well‐studied models. We conclude that RNA localization is a widespread and conserved mechanism that generates localized protein enrichments with far‐reaching consequences for cellular activity and function At the nexus of specialized cellular responses are localized enrichments of protein activity. The localization of messenger RNA (mRNA) coupled with translational control often plays a crucial role in the generation of protein concentrations at defined subcellular domains. Although mRNA localization is classically associated with large specialized cells, such as neurons and embryos, RNA localization is a highly conserved paradigm of post‐transcriptional regulation observed in diverse cellular contexts. Functions of localized mRNAs extend far beyond the well‐studied examples of neuronal polarization and developmental patterning. Since the initial discovery of the intracellular localization of cytoskeletal mRNAs within migrating cells, hundreds of mRNAs are now known to be enriched at specific organelles where they contribute to cell function. In this short review, we discuss basic principles regulating RNA localization and consider the contribution of localized mRNA to several essential cellular behaviors. We consider RNA localization as a mechanism with widespread implications for cellular function.